2023
DOI: 10.3389/fpubh.2023.1102618
|View full text |Cite
|
Sign up to set email alerts
|

Study characteristical and regional influences on postpartum depression before vs. during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: BackgroundWhile the public is under serious pressure from the coronavirus disease 2019 (COVID-19), the final impact and possible contributing factors to postpartum depression symptoms (PPDS) remain unknown. Therefore, a meta-analysis to investigate the association between PPDS and the COVID-19 pandemic was carried out by comparing the data between pre-pandemic and post-pandemic timeframes and exploring the influencing factors.MethodsThis systematic review was prospectively registered and recorded in a study pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…North American studies (8). Other studies from various parts of the world, including Turkiye, have revealed a relationship between the pandemic and PPD.…”
Section: Introductionmentioning
confidence: 97%
“…North American studies (8). Other studies from various parts of the world, including Turkiye, have revealed a relationship between the pandemic and PPD.…”
Section: Introductionmentioning
confidence: 97%
“… 17 In contrast, another meta-analysis exploring the relationship between PPD and the COVID-19 pandemic, comparing data from before and after the pandemic, revealed a higher prevalence of PPD associated with the epidemic. 18 It is noteworthy that few systematic reviews have directly compared the effects of the COVID-19 pandemic on PPD among women, and there is a lack of such reviews in the context of LMICs including Uganda.…”
Section: Introductionmentioning
confidence: 99%